2005
DOI: 10.1084/jem.20050265
|View full text |Cite
|
Sign up to set email alerts
|

Properties and protective value of the secondary versus primary T helper type 1 response to airborne Mycobacterium tuberculosis infection in mice

Abstract: Mice immunized against Mycobacterium tuberculosis (Mtb) infection by curing them of a primary lung infection were compared with naive mice in terms of the ability to generate a Th1 cell immune response and to control growth of an airborne Mtb challenge infection. Immunized mice generated and expressed Th1 cell immunity several days sooner than naive mice, as demonstrated by an earlier increase in the synthesis in the lungs of mRNA for Th1 cytokines and for inducible nitric oxide synthase, an indicator of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
161
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 39 publications
16
161
0
Order By: Relevance
“…Rapid accumulation of specific IFN-␥-secreting CD8 ϩ T cells is in line with previous observations of accelerated accumulation of CD8 ϩ T cells and early IFN-␥ production in tissues of vaccinated or infected and cured mice (13)(14)(15)18). At later time points after challenge, nonvaccinated mice showed similar numbers of specific IFN-␥ secreting CD8 ϩ T cells when compared with vaccinated mice.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Rapid accumulation of specific IFN-␥-secreting CD8 ϩ T cells is in line with previous observations of accelerated accumulation of CD8 ϩ T cells and early IFN-␥ production in tissues of vaccinated or infected and cured mice (13)(14)(15)18). At later time points after challenge, nonvaccinated mice showed similar numbers of specific IFN-␥ secreting CD8 ϩ T cells when compared with vaccinated mice.…”
Section: Discussionsupporting
confidence: 76%
“…At the plateau phase of M. tuberculosis infection, frequencies of Ag85-specific IFN-␥ secreting CD4 ϩ T cells correlated with mycobacterial load in tissues rather than with protection. This lack of correlation of specific CD4 ϩ T cells with protection was unexpected, because CD4 ϩ T cell responses, in particular, IFN-␥ secretion, are considered pivotal for control of tuberculosis (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although immunological memory induced by M. tuberculosis can provide short-term protection as indicated by a reduction in the bacterial burden following rechallenge, some data suggest that long-term protective memory to M. tuberculosis does not efficiently develop in experimentally infected animals (20,42). The reinfection of patients previously treated for tuberculosis also challenges the notion that prior exposure to M. tuberculosis induces protective immunity (7,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 66%
“…This is known to be crucial for host protection against MTB infection [52][53][54]. Hwang, et al demonstrated in vitro that addition of lactoferrin on activated macrophages leads to increase IL-12 production while at the same time reducing IL-10 [25,33].…”
Section: Discussionmentioning
confidence: 99%